2018
DOI: 10.1177/1368430218801078
|View full text |Cite
|
Sign up to set email alerts
|

Being nice isn’t enough: Prosocial orientation and perceptions of self-uniqueness jointly promote outgroup reparation

Abstract: Using a real-life case of intergroup victimization (i.e., victimization of migrant workers in Korea), we tested our hypothesis that positive attitudes toward compensating a victimized outgroup and intention to participate in ingroup corrective actions would be facilitated when a prosocial orientation is combined with high levels of perceived self-uniqueness. In Study 1, we measured participants’ social value orientation and their self-attributed need for uniqueness as our independent variables ( N = 249) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Lantian et al, 2017). Choi and Euh (2019) showed that the activation of self-uniqueness can promote outgroup reparation among members of the advantaged group when combined with a prosocial orientation. The current research reinforces the evidence that the need to be unique can have prosocial consequences, in this case, by motivating collective action for equality among members of the disadvantaged ingroup.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lantian et al, 2017). Choi and Euh (2019) showed that the activation of self-uniqueness can promote outgroup reparation among members of the advantaged group when combined with a prosocial orientation. The current research reinforces the evidence that the need to be unique can have prosocial consequences, in this case, by motivating collective action for equality among members of the disadvantaged ingroup.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Lantian et al, 2017; Mok & Morris, 2009). For instance, Choi and Euh (2019) primed self‐uniqueness and then measured support for outgroup compensation and willingness to engage in ingroup corrective actions. The authors reasoned that self‐uniqueness might help members of the perpetrator group to distance themselves from the normative, defensive position of the dominant ingroup and use their independence in favour of the victimized outgroup.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has treated the Big five personality of agreeableness as a dispositional proxy for pro-social motivation (e.g. Bechtoldt et al , 2010; Choi and Euh, 2019). Participants were given the following eight adjectives: cold, cooperative, harsh, kind, rude, sympathetic, warm and unsympathetic (Palmer and Loveland, 2004; Saucier, 1994).…”
Section: Research Overviewmentioning
confidence: 99%
“…However, previous research has identified the moderating variables that reinforce or inhibit the effect of pro-social motivation on interpersonal behavior (e.g. power, Chen et al , 2001; the need for uniqueness, Choi and Euh, 2019). These findings suggest that the positive effect of pro-social motivation on HCNs’ support to expatriates may be qualified by other variables.…”
Section: Introductionmentioning
confidence: 99%
“…This has sometimes caused confusion in the literature (see Cross et al, 2011) and misspecification of the effects associated with the two variables (see Wagner, 2002). However, a growing body of research shows that, on the individual level, the two constructs are conceptually distinct (see Brewer & Chen, 2007; Kağitçibaşi, 2005; Wagner, 2002), and that in a group context, the perception of self as an independent (vs. interdependent) entity can be paired with a belief in the priority of either the group’s or one’s own personal goals (Bechtoldt et al, 2012; Choi et al, 2018; Choi & Euh, 2018; Choi et al, 2019; Choi & Yoon, 2018). In this regard, our data lend further support for the synergy model that stipulates a joint positive effect that results from a combination of independence in self-concept and collectivistic values in collaborative work settings.…”
Section: The Current Researchmentioning
confidence: 99%